From Single- to Multi-organ-on-a-Chip System for Studying Metabolic Diseases - Jang, Minjeong; Kim, Hong Nam (Biochip journal, 2023)
Metabolic diseases have been a major public health issue and a clinical challenge worldwide. Dysfunction of metabolic homeostasis is linked to the onset of various diseases because the various metabolizing organs synchronously interact to maintain metabolic homeostasis. Therefore, understanding inter-organ communication is important to develop more accurate drug testing and discovery for the treatment of metabolic diseases. The physiologically relevant organ-on-a-chip system is an emerging technology to study metabolic dynamics by providing an organ-level platform. This review summarizes the single- and multi-organ chip systems to study metabolic diseases and their dynamics, focusing on their inter-organ crosstalk.